POLA KALIMAT PERINTAH DALAM BAHASA KAILI - Muh. Asri B. (Multilingual, 2016)
The aim in the study is describing imperative sentence pattern of Kaili language. The method which is appliedare field reseach and descriptive method. The methods are applied in order researcher can observe, listen,note down, and record the imperative sentence of Kaili Language. Descriptive method is applied according tothe data of the speakers. The result of analysis indicates that there are ten imperative sentence pattern of KailiLanguage : (1) imperative sentence pattern of order, (2) imperative sentence pattern of request, (3) imperativesentence pattern of prohibition, (4) imperative sentence pattern of suggestion, (5) imperative sentence patternof request, (6) imperative sentence pattern of consideration, (7) imperative sentence pattern of coercion, (8)imperative sentence pattern of persuasion (9) imperative sentence pattern of demand, and (10) imperative sentence pattern of insistence.